Promoting Research Excellence in Down Syndrome: Proceedings of the 5th International Conference of the Trisomy 21 Research Society - Fabio Di Domenico; Marzia Perluigi; Antonella Tramutola; Maria Giulia Bacalini; Daniella Balduino Victorino; Isabel Barroeta; Renata Bartesaghi; Angelo Carfi; Maria Carmona-Iragui; Ann D. Cohen; Alberto C. S. Costa; Floriana Costanzo; et al. (NeuroMolecular Medicine, 2026)
Down syndrome (DS), or trisomy 21 (T21), represents the most common genetic cause of intellectual disability worldwide and is associated with a wide range of medical, developmental, and neurodegenerative conditions, including a universal predisposition to early-onset Alzheimer’s disease (AD). Since its establishment in 2014, the Trisomy 21 Research Society (T21RS) has provided a global forum for advancing DS research across disciplines and promoting translational efforts to improve health and quality of life. Every two years, T21RS hosts an international scientific meeting that brings together researchers, clinicians, self-advocates, families, and industry stakeholders. In 2024, the 5th T21RS International Conference was held in Rome, Italy, from June 5 to 8, under the theme “Promoting Research Excellence in Down Syndrome.” The meeting brought together about 500 scientists from 26 countries across five continents, and more than 900 attendees overall, including families and caregivers. The scientific program featured 5 keynote lectures, 2 satellite meetings, 17 symposia, 7 nano symposia, 2 workshops, and 1 industry-focused session, totaling more than 150 oral presentations. More than 230 abstracts were presented as posters. The conference covered research across the lifespan of individuals with DS, spanning genomic and epigenetic regulation, molecular and cellular mechanisms, preclinical and experimental models, cognition and behavior, neurodevelopment, aging and neurodegeneration, co-occurring medical conditions, and therapeutic interventions. Dedicated sessions focused on capacity-building in DS research and societal engagement were established. Significantly, T21RS promoted inclusivity by supporting 60 young investigator fellowships, providing childcare awards, and organizing a two-day program for families and caregivers in collaboration with Italian DS associations. This proceeding summarizes the main scientific highlights of the 5th T21RS International Conference, reflecting the latest advances in DS biology, clinical research, biomarker development, and therapeutic innovation.